Orally disintegrating film: a review of its formulation and manufacturing method - Liew, Kai Bin; Gobal, Ganesan; Mohd Rofiq, Hanifah; Phang, Hiu Ching; Lee, Siew-Keah; Ming, Long Chiau; Helal Uddin, A.B.M.; Chew, Yik Ling; Lakshminarayanan, Vijayakumar (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2023)
Oral route drug delivery system is still considered as the most convenient and patient friendly drug delivery route. Over the decades, many research has been performed to improve the functionality oral dosage form. Orally disintegrating film (ODF) is a newer oral drug delivery system, which is in the form of a thin film that will disintegrate in the oral cavity within a matter of seconds. The aim of this review paper is to recap ODF, its benefits, formulation contents and manufacturing method. With more research and development work has been conducted on ODF, the dosage form is expected to be manufactured and scaled up to be commercializable products to be sold in the market.